Reorientasi Perlindungan Kekayaan Intelektual Perguruan Tinggi: Membangun Ekosistem Inovasi yang Berkeadilan melalui Pengabdian kepada Masyarakat di Lingkungan LLDIKTI Wilayah I Sumatera Utara - Muhammad Citra Ramadhan; Fitri Yanni Dewi Siregar (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Intellectual property (IP) protection in higher education institutions has largely been viewed as an administrative requirement focused on documentation and registration volume. This creates a paradox, as increasing research outputs are not matched by adequate legal protection, innovation downstreaming, and societal utilization of research results. Therefore, a reorientation is needed to position IP protection as a strategic instrument for building a fair innovation ecosystem. This community engagement program was conducted in LLDIKTI Region I institutions through presentations, discussions, and strengthening IP center capacity. Activities focused on mapping IP systems, identifying management challenges, and reinforcing a paradigm oriented toward innovation downstreaming and public benefit. Results show improved participant understanding of shifting IP protection from an administrative to a strategic approach. IP is increasingly recognized as a tool for innovation, technology transfer, and institutional competitiveness. This reorientation emphasizes inventor rights protection, fair benefit distribution, and broader public access to innovation within a sustainable and equitable ecosystem.